A guide to stock control - Battersby, Albert (London : Pitman, 1970)
This book comprises a menu of inventory analysis and is intended for the mathematically unsophisticated reader and inventory control concepts for non-specialists.
lje 22/1/19
Loans
Keywords: Stores; Stock-room keeping